Maasai gender in typological perspective - Doris Payne (Studies in African Linguistics)
Maasai nouns (or determined NPs) occur in one of three genders: masculine/ augmentative, feminine/diminutive, or place (the last is extremely limited). The Maasai gender system is semantic rather than formal (i.e., based on phonological or morphological criteria) in type, but with at least two distinct semantic subtypes. For a restricted set of nouns, gender is immutably based on lexical semantic features. Other nouns are lexically neutral, or have a default gender specification which can be overridden by the speaker's construal of the referent as small/ female, large/male, or pejorative. Varying by the noun, either of the productive genders may convey a pejorative construal, though it is most common in the feminine. The default gender of a noun is that which yields the non-pejorative sense. Some evidence suggests that feminine is becoming the grammatically unmarked gender.